Pengelolaan Sarana dan Prasarana Pendidikan - Miptah Parid; Afifah Laili Sofi Alif (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2020)
Madrasas as a type of school education institution have the same duties andresponsibilities as other educational institutions that are under the guidance ofthe Ministry of Education and Culture. In order for education in the madrasas tobe effective, a complete and well-organized educational facility can be used asfully as possible to support a quality teaching and learning process. Based on thedescription of the discussion, a summary of conclusions is obtained: (1)Management of educational facilities and infrastructure is structuring activities,starting from the needs, procurement, inventory, storage, maintenance, use andstorage of complete arrangement of land, buildings, equipment, and schoolequipment available for and target. (2) Types of education can be divided intolearning tools and educational media. While the two types of infrastructure arebuildings and furniture. (3) The purpose of managing educational facilities andinfrastructure, is the provision of professional facilities and services in the field offacilities and infrastructure in schools in order to realize the education process inschools effectively and efficiently. (4) Planning space and educationalinfrastructure, namely planning, procurement, maintenance, inventory, andelimination